Kinetics of Carbothermal Reduction Process of Different Size Phosphate Rocks - Li Pengfei (De Gruyter, 2021)
The effects of particle size on the apparent kinetics of carbothermal reduction process of phosphate rock were studied by non-isothermal thermogravimetric analyses. Phosphate rock of various particle size was reacted with coke and silica under high purity argon atmosphere. The apparent kinetic model and parameters of carbothermal reduction reaction of phosphate rock with different particle sizes were derived by combination of model-free (Flynn–Wall–Ozawa, Kissinger–Akahira–Sunose, Tang, Starink) and model-fitting (Coats-Redfern, Master-plots) methods. The results showed that the obtained apparent activation energy of reaction reduces from 371.74 kJ/mol to 321.11 kJ/mol as the particle size of phosphate rock decreasing from 100–150 μm to 38–48 μm. The reaction apparent kinetics was found to follow shrinking-core model and the conversion degree function equation is G(α)=1−(1−α)12G\left( α \right) = 1 - {\left( {1 - α } \right)^{{1 \over 2}}} (α is conversion degree and G(α) is integral form of conversion degree function).